The Mediating Role of Organizational Culture in the Relationship Between Leadership Frameworks and Job Satisfaction Among Police Officers in Palestine - Taysir Yousef Diab Ostaali (Universiti Sains Islam Malaysia, 2024)
Matric:4191165 (FKP)